MENGGUNAKAN MEDIA WOODEN HOUSE DALAM MEMPELAJARI INTRODUKSI BANGUN RUANG DAPAT MENINGKATKA N ILAI BELAJAR SISWA KELAS X.A-2 SMA NEGERI 8 BANDA ACEH TAHUN PELAJARAN 2017/2018 - Kasmawati Kasmawati (Jurnal Peluang, 2019)
Learning media is a tool in giving examples directly in the learning process. The purpose of this study was to determine the use of wooden house media as a medium in studying the mathematics of introductory building materials. Research subjects Class X. A-2 SMA Negeri 8 Banda Aceh Academic Year 2017/2018 with the number of students 24 students consists of 17 men, and 6 female students. In general, viewed from various aspects, this class is very heterogeneous. The research procedure is to carry out a research cycle that begins with planning, implementing, observing and also reflecting on the research results. The results of the research are Cycle I meeting 1 with the average value of affective aspects C, cognitive aspects 6.54 and psychomotor 6.58% this value cannot be stated classically. The 2nd meeting of the average value in the affective aspect C, cognitive aspects 6.88 and psychomotor aspects 6.79. The mastery learning value is 54.29%. Cycle II encounters the average value on the B affective aspects, cognitive aspects 7.13 and psychomotor 6.92. For the mastery learning value reached 66.7%. The second meeting of the average value on the B affective aspects, 7.38 cognitive aspects and 7.17 psychomotor aspects of learning completeness reached 79.2%.